Cell Wall Stress Stimulates the Activity of the Protein Kinase StkP of Streptococcus pneumoniae, Leading to Multiple Phosphorylation - Ulrych, Aleš; Fabrik, Ivo; Kupčík, Rudolf; Vajrychová, Marie; Doubravová, Linda; Branny, Pavel (Journal of molecular biology, 2021)
Streptococcus pneumoniae is an opportunistic human pathogen that encodes a single eukaryotic-type Ser/Thr protein kinase StkP and its functional counterpart, the protein phosphatase PhpP. These signaling enzymes play critical roles in coordinating cell division and growth in pneumococci. In this study, we determined the proteome and phosphoproteome profiles of relevant mutants. Comparison of those with the wild-type provided a representative dataset of novel phosphoacceptor sites and StkP-dependent substrates. StkP phosphorylates key proteins involved in cell division and cell wall biosynthesis in both the unencapsulated laboratory strain Rx1 and the encapsulated virulent strain D39. Furthermore, we show that StkP plays an important role in triggering an adaptive response induced by a cell wall-directed antibiotic. Phosphorylation of the sensor histidine kinase WalK and downregulation of proteins of the WalRK core regulon suggest crosstalk between StkP and the WalRK two-component system. Analysis of proteomic profiles led to the identification of gene clusters regulated by catabolite control mechanisms, indicating a tight coupling of carbon metabolism and cell wall homeostasis. The imbalance of steady-state protein phosphorylation in the mutants as well as after antibiotic treatment is accompanied by an accumulation of the global Spx regulator, indicating a Spx-mediated envelope stress response. In summary, StkP relays the perceived signal of cell wall status to key cell division and regulatory proteins, controlling the cell cycle and cell wall homeostasis.
Keywords: Bacterial Proteins; fosforylace; proteom; antibakteriální látky; Phosphorylation; phosphoproteome; proteinkinasy; peptidoglycan synthesis; fosfoproteiny; Phosphoproteins; Stress, Physiological; Protein Kinases; buněčná stěna; eukaryotic-like Ser/Thr protein kinase; Cell Wall; Anti-Bacterial Agents; cell division; β-lactam; bakteriální proteiny; Streptococcus pneumoniae; fyziologický stres; Proteome